Mental Health Differences Between Older and Younger Lesbian, Gay, Bisexual, and Transgender Veterans: Evidence of Resilience. Issue 2 (15th March 2019) - Cortes, Jose; Fletcher, Terri L.; Latini, David M.; Kauth, Michael R.
ABSTRACT: Objective : To examine health and identity differences between older (50+) and younger (< 50) lesbian, gay, bisexual, and transgender (LGBT) veterans. Methods : Participants (N = 254 ) completed an internet survey assessing depression, anxiety, alcohol use, identity, minority stress, and outness. T tests and logistic regression were used to analyze results. Results : Older LGBT veterans reported less alcohol use ( p < .01) than younger counterparts. No age differences in depression or anxiety were reported. Older participants reported LGBT identity as more central to their overall identity ( p < .01) and having less minority stress ( p < .05), than younger participants. Conclusions : Compared to younger LGBT veterans, older LGBT veterans appeared more resilient over stressors that can impact mental health. Overall older LGBT veterans experienced less alcohol use and reported less minority stress than younger veterans. LGBT identity was more central to older veterans' overall identity than younger Veterans. Clinical Implications : LGBT veterans may experience stressors that can impact mental health, although older LGBT veterans show remarkable resilience. Clinicians should assess sexual orientation and gender identity, as well as veteran status, of patients in order to best evaluate their health risks and strengths.